Peningkatan pengetahuan etika beserta standar operasional prosedur dalam bisnis dan strategi pemasaran UMKM - Setiabudi, Dedet Hermawan; Subarjo, Abdul Haris (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2022)
This community service activity is a collaboration between academics and MSME entrepreneurs. The purpose of the activity is for MSME entrepreneurs, alumni of the Adisutjipto Aerospace Technology Institute to gain knowledge about ethics and codes of conduct, especially in terms of doing business. Besides discussing ethics and code of ethics, it also discusses standard operating procedures in managing business. It is hoped that the discussion of standard operating procedures can improve the quality of MSME products produced and can increase sales. The next discussion is about marketing strategies either through opening outlets/stores or by using social media and the internet. This community service activity uses a webinar because of the world situation due to the covid 19 health disaster. To find out the response of the webinar participants at the end of the activity, questions are asked with a questionnaire, from the results of the questionnaire with the question whether the activity is interesting there are 92% of participants answering interesting activities, 4% not interesting, 2% answered normal and 2% did not answer. participants in community service activities were also given questions about the answers of the speakers to questions from 94% of participants answered that the speakers gave good answers and 6% of participants answered that the speakers did not give good answers. In addition, a SWOT analysis was also carried out on partners in community service activities to obtain an overview of partners' strengths, weaknesses, opportunities and challenges.